1979
DOI: 10.1007/bf01441624
|View full text |Cite
|
Sign up to set email alerts
|

The reaction238U +238U at 7.42MeV/u

Abstract: One-particle-inclusive measurements have been performed for the charge, kinetic energy and angular distributions of reaction products from 23 B U + 238 U at 1 766MeV (7.42MeV/u) incident energy. The deep inelastic products exhibit features similar to those seen in reactions induced by medium heavy nuclei: increasing particle transfer is observed with increasing energy damping, the angular distributions are peaked near the grazing angle, they broaden significantly with increasing energy loss and/or charge trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
83
0

Year Published

1981
1981
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 23 publications
(16 reference statements)
5
83
0
Order By: Relevance
“…These reactions were extensively studied experimentally in the 1980s [3][4][5][6][7][8]. (An in-depth review of these data is found in [9].)…”
Section: Introductionmentioning
confidence: 99%
“…These reactions were extensively studied experimentally in the 1980s [3][4][5][6][7][8]. (An in-depth review of these data is found in [9].)…”
Section: Introductionmentioning
confidence: 99%
“…Experimental results supporting the above described hypotheses can be found in [3]. In this experiment [3], inclusive one particle measurements were performed for the charge, the kinetic energy and the angular distributions of the reaction products from 238 U+ 238 U at 7.42A MeV. Relatively large mass transfers have been found for deep inelastic reactions with the largest Q-values.…”
Section: Decay Channelsmentioning
confidence: 64%
“…it will be very difficult to isolate it from quasielastic or deep inelastic processes. Experimental results supporting the above described hypotheses can be found in [3]. In this experiment [3], inclusive one particle measurements were performed for the charge, the kinetic energy and the angular distributions of the reaction products from 238 U+ 238 U at 7.42A MeV.…”
Section: Decay Channelsmentioning
confidence: 66%
See 1 more Smart Citation
“…These reactions were studied extensively about thirty years ago. Among other topics, there had been great interest in the use of heavy-ion transfer reactions to produce new nuclear species in the transactinide region [17][18][19][20][21][22]. The cross sections were found to decrease very rapidly with increasing atomic number of surviving heavy fragments.…”
Section: Transfer Reactionsmentioning
confidence: 99%